Noradrenaline Modulates the Membrane Potential and Holding Current of Medial Prefrontal Cortex Pyramidal Neurons via β1-Adrenergic Receptors and HCN Channels - Grzelka, Katarzyna; Kurowski, Przemysław; Gawlak, Maciej; Szulczyk, Paweł (Frontiers in Cellular Neuroscience, 2017)
The medial prefrontal cortex (mPFC) receives dense noradrenergic projections from the locus coeruleus. Adrenergic innervation of mPFC pyramidal neurons plays an essential role in both physiology (control of memory formation, attention, working memory and cognitive behavior) and pathophysiology (attention deficit hyperactivity disorder, posttraumatic stress disorder, cognitive deterioration after traumatic brain injury, behavioral changes related to addiction, Alzheimer’s disease and depression). The aim of this study was to elucidate the mechanism responsible for adrenergic receptor-mediated control of the resting membrane potential in layer V mPFC pyramidal neurons. The membrane potential or holding current of synaptically isolated layer V mPFC pyramidal neurons was recorded in perforated-patch and classical whole-cell configurations in slices from young rats. Application of noradrenaline, a neurotransmitter with affinity for all types of adrenergic receptors, evoked depolarization or inward current in the tested neurons irrespective of whether the recordings were performed in the perforated-patch or classical whole-cell configuration. The effect of noradrenaline depended on β1- and not α1- or α2-adrenergic receptor stimulation. Activation of β1-adrenergic receptors led to an increase in inward Na+ current through HCN channels, which carry a mixed Na+/K+ current. The protein kinase A and C-, glycogen synthase kinase-3β- and tyrosine kinase-linked signaling pathways were not involved in the signal transduction between β1-adrenergic receptors and HCN channels. The transduction system operated in a membrane-delimited fashion and involved the βγ subunit of G protein. Thus, noradrenaline controls the resting membrane potential and holding current in mPFC pyramidal neurons through β1-adrenergic receptors, which in turn activate HCN channels via a signaling pathway involving the βγ subunit.